COMPUTER BASED ASSESSMENT SYSTEM FOR EVALUATING SUBJECTIVE QUESTIONS - Evwiekpaefe, Abraham Eseoghene; Muhammad, Yahya Umar (FUDMA JOURNAL OF SCIENCES, 2021)
With the increase in the number of students in our tertiary institutions coupled with the number of courses offered in the various universities, the management of examination processes has become more complex in terms of resources, time and manpower. This has resulted to the rapid adoption of a computerized means of conducting examinations instead of the traditional pen and paper. However, this computer-based technique currently used in our tertiary institutions in assessing studentsâ€™ examination handles only the multiple choice questions (MCQ). This paper therefore is aimed at designing and implementing a simplified algorithm that assesses subjective (descriptive) type questions. Keyword and synonym matching techniques were used as the method for creating the simplified algorithm for the assessment of the subjective answers. The algorithm was designed using the Unified Modeling Language.   The application was built in the NetBeans IDE version 8.2 with Java as the main programming language. Spring Boot Framework with Thymeleaf View Engine was used as the Web development Framework. MySQL was used for the database while HTML, CSS and JavaScript were used for building the web page interface. For the synonyms, grammar and spell checking, Merriam-Webster Dictionary API and Language Tool API were used. A prototype system was consequently developed, tested and various results shown.